Discourse Subaltern dalam Masyarakat Interkultural: Mencermati Relasi Gender Jilbab dan Perempuan Berjilbab di Prancis - Udasmoro, Wening (Jurnal Ilmu Sosial dan Ilmu Politik, 2010)
After 11 September 2001, hijab and women with hijab have become the new subaltern in the contemporary social and cultural relationships in France. It is interesting to see how political elites, society and women with hijab are seeing those symbols as part of their subject positionâemphasizing the concept of âselfâ and âothersâ. This paper is based on research which employed Critical Discourse method, specifically to examine the level of actorâs positioning in order to elaborate how positioning is used to examine the dynamics of social relation in France, including the various forms of its transformation and its resistence.